Dari Postmodernisme ke Dekolonialitas: Kritik atas Wacana Tafsir Gender dalam Kajian Al-Qur’an Kontemporer melalui Pembacaan QS. 4:34 dalam Tafsir Awal - Iffah Al Walidah; Nafisatul Mu'awwanah (Universitas Islam Negeri Sunan Kalijaga, 2025)
This article examines the discourse of gender exegesis in contemporary Qur’anic studies through a decolonial critique of Islamic feminist epistemology, focusing on the interpretation of Q. 4:34 within the early exegetical tradition. It departs from the thesis that Islamic feminism, while significantly contributing to the deconstruction of patriarchal interpretations, continues to operate within a postcolonial horizon that risks reproducing the coloniality of knowledge. Employing hermeneutical tools such as historical contextualization, intra-textual reading, and a tawhidic paradigm, Islamic feminism advances an egalitarian moral vision of the Qur’an and interprets gender hierarchy as a product of exegetical construction. However, this project also entails epistemological tensions, as it often marginalizes pre-modern exegesis as a residue of patriarchy and promotes an anachronistic reading that evaluates Islamic tradition through modern ethical standards. Through a decolonial lens, this study repositions early tafsir as a legitimate and authoritative hermeneutical partner by demonstrating that classical exegetes possessed coherent methodological foundations and articulated a rational pre-modern moral cosmology within their historical context. In interpreting Q. 4:34, gender relations in early Muslim society are understood as structured upon ethical responsibility and God-consciousness, wherein men and women perform distinct yet complementary roles in a just framework. Accordingly, this article argues that the decolonization of Qur’anic studies necessitates the restoration of the epistemic authority of the classical exegetical tradition.